An Analysis of Culture Shock and the Coping Strategies in the Outsourced Movie - Agnes Salsabilla; Putri Rindu Kinasih (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Culture shock is a phenomenon that is experienced by someone who moves to an environment with a culture that is different from their own just as happened to Todd Anderson in the Outsourced movie. This study used a qualitative method to analyze the main character, Todd Anderson, who was sent to India from America. Todd went through five stages of culture shock based on Adler’s theory. In the contact stage, he was still integrated with his American culture. In the second stage, Todd experienced stress and frustration as his ability to relate, connect, and engage with others fell apart. He also felt alienated from the Indian locals. Todd looked for a relationship with the Americans during the third stage. In the fourth stage, Todd freed himself from previous defensiveness towards Indian culture. In the fifth stage, Todd was able to build trust and sensitivity to the Indians, and Todd accepted all the similarities and differences between Indian culture and American culture. Todd also applied all strategies based on Plummer’s theory. Todd looked for a new support group and enriched his life in India. Todd then discovered Indian social taboos that should be avoided. Finally, Todd developed an understanding of Indian culture. Overall, this study concludes that although culture shock occurs in stages, it can be overcome through embracing the local way of life, as Todd did in the film, and ceasing to reject it.